Respuesta :

Hi!

Answers of 5;

(a)

(3a - 2)² = 9a² - 12a + 4

(3a - 2)² = (3a - 2)(3a - 2) = 9a² - 12a + 4

The formula for this is;

(x - y)² = x² - 2xy + y²

(b)

(5 + 2p)² = 25 + 20p + 4p²

(5 + 2p)² = (5 + 2p)(5 + 2p) = 25 + 20p + 4p²

The formula for this is;

(x + y)² = x² + 2xy + y²

(c)

(8 - 5m)² = 64 - 80m + 25m²

(8 - 5m)² = (8 - 5m)(8 - 5m) = 64 - 80m + 25m²

The formula for this is;

(x - y)² = x² - 2xy + y²

Answers of 6;

(a)

(y + 7)(y - 7) = y² - 7² = y² - 49

The formula for this is;

x² - y² = (x + y)(x - y)

(b)

(2x - 3)(2x + 3) = (2x)² - 3² = 4x² - 9

The formula for this is;

x² - y² = (x + y)(x - y)

(c)

(4m - 5)(4m + 5) = (4m)² - 5² = 16m² - 25

The formula for this is;

x² - y² = (x + y)(x - y)

==> Sorry, my English is bad, I'm trying to learn this language.

Wish Good Lessons! ^-^